Effect of structured physical activity on intelligence in underperforming school students - R., Vishnupriya; D., Kannan; K., Anantharaj; Murugaiyan, Poovarasan; Umasankar, Yamini; Vianni, Diovin Derose; Suganthirababu, Prathap (International Journal of Research in Medical Sciences, 2025)
Background: Poor academic performance in some children often stems from lack of concentration. Traditional measures like extra classes and repeated tests show questionable effectiveness. Exercise, however, may offer an alternative, as it enhances cognitive skills and academic performance. This study aims to examine the effect of structured physical activity (SPA) on intelligence in underperforming school students. Methods: This experimental study was conducted among VI-X standard students from schools in Komarapalayam, Namakkal district. Eligible participants were 11-15 years old, full-time students from middle or low socio-economic groups. From 220 screened students (168 boys, 52 girls), 50 were selected. After obtaining parental consent, they were randomly allocated into two groups: SPA, n=25; 15 boys, 10 girls and general PA (GPA, n=25; 17 boys, 8 girls). The intervention was integrated into the school curriculum. Outcomes measured were intelligence (Bhatia battery test) and endurance, assessed at baseline and at alternate weeks over an 8-week period. Data analysis was performed using SPSS 26.0, with p<0.05 considered statistically significant. Results: The result of the study shows considerable significance in both groups, where there is a remarkable improvement in the SPA group with t value of 7.67 (p<0.005), compared with GPA with t value of 8.44 (p<0.005). Conclusions: This study concluded that SPA improves the activity on intelligence in underperforming school students when it was compared with regular PA.